The Letter of Aristeas 'Aristeas to Philocrates' or 'On the Translation of the Law of the Jews' - Aristeas Epistolographus 3 v. Chr.; Wright, Benjamin G. 1953- (Berlin Boston De Gruyter, 2015)
In modern scholarship, there has been no fully fledged commentary written on the Letter of Aristeas, an important work of Hellenistic Judaism in Alexandria, which contains the earliest version of the translation of the Septuagint. This volume fills that gap. The book will be of relevance to anyone interested in Hellenistic Judaism, the Septuagint, the ancient Jewish community in Alexandria or ancient Jewish paideia. Benjamin G. Wright III, Lehigh University, Bethlehem, PA, USA.
Frontmatter -- Preface -- Table of Contents -- I. INTRODUCTION -- II. GENERAL BIBLIOGRAPHY -- III. TRANSLATION AND COMMENTARY -- Preface (§§ 1–8) -- The Library Project (§§ 9–11) -- The Liberation of the Jewish Slaves (§§ 12–27) -- Demetrius’s Report (§§ 28–34a) -- Ptolemy II’s Letter to Eleazar (§§ 34b–40) -- Eleazar’s Reply to Ptolemy (§§ 41–51a) -- The Construction of the King’s Gifts (§§ 51b–82) -- Jerusalem and its Environs (§§ 83–120) -- Eleazar’s Farewell to the Translators (§§ 121–127) -- Eleazar’s Apologia for the Law (§§ 128–171) -- The Reception of the Translators at Alexandria (§§ 172–186) -- Excursus on Aristeas, Hellenistic Symposia and Peri Basileus Literature (Part 1) -- The Symposia (§§ 187–300) -- Excursus on Aristeas, Hellenistic Symposia and Peri Basileus Literature (Part 2) -- Aristeas’s Praise of the Translators (§§ 295–300) -- The Execution of the Translation (§§ 301–307) -- The Proclamation of the Translation (§§ 308–316) -- The Departure of the Translators (§§ 317–321) -- Epilogue (§ 322) -- Abbreviations -- Index of Names and Subjects -- Index of Ancient Sources -- Index of Modern Authors
Description based upon print version of record
Keywords: Electronic books; Electronic books